Environmental Conflict as a Socio-Legal Phenomenon - Yaremak, Zoryana (Journal of Vasyl Stefanyk Precarpathian National University, 2018)
The article studies environmental conflict and identifies it as a specific socio-legal phenomenon – legal environmental conflict  on the basis of the suggested unified approach to understanding its nature. It is confirmed that legal conflict has to be studied in terms of the inseparable unity of its social basis and legal nature. It is concluded that the generic features of social conflict in the process of juridization turn into features of legal nature and acquire legal character in legal conflict. The distinction is made between the notions of “legal conflict” and “legal collision”.